Cloud Based Automated Identification and Development to Provide Compatibility and Security for Cross Browser in Web Application - MK, Roshne; Sardar, Shaikh Afreen Md; K, Tulsi; Dayanidhi, Varshini C; H, vinod (International Journal of Computer Sciences and Engineering, 2025)
A good Website is more than just something to look at, it is functional interactive and flawless. As technologies are becoming smart so we need to be smarter enough to utilize them. With the rapid evolution of web technologies, the complexity of web applications has also grown up. Specially making a web application that works well with cross browser is a great challenge. Clearly, cross-browser means something works with all versions of all browsers to have existed since the web began. By this paper we have pointed out some reasons why applications behave or appear differently in different browsers because if you know the cause, you can get a solution.